The Role of Islamic Religious Education Learning in Shaping the Social Awareness of Students in Elementary Schools - Sudarmin, Sudarmin; Muis, Andi Abd.; Maallah, Muhammad Nur; Idris, Mahsyar; Naim, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the cultivation and implementation of Islamic Religious Education (PAI) learning in shaping students' social awareness, and to identify the challenges faced at UPT SD Negeri 180 Kalimbua, Enrekang Regency. A descriptive qualitative approach was employed, with data gathered through participatory observation, in-depth interviews, and documentation. Informants consisted of the principal, two PAI teachers, four homeroom teachers for grades III–VI, and ten selected students. The findings reveal that: (1) PAI values were cultivated integratively and progressively by linking Islamic teachings to concrete social actions across grade levels; (2) PAI learning was implemented through inclusive, contextual, and social project-based approaches involving active parental and community participation; (3) primary challenges included student background heterogeneity and unsupportive external environments, addressed through adaptive, community-based collaborative strategies. This study concludes that integrated PAI learning significantly shapes empathy, caring, responsibility, and students' active participation in social life.